2015
DOI: 10.1016/j.vaccine.2015.08.043
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review of adverse events following immunization during pregnancy and the newborn period

Abstract: In 2013, the WHO Strategic Advisory Group of Experts on Immunization (SAGE) requested WHO to develop a process and a plan to move the maternal immunization agenda forward in support of an increased alignment of data safety evidence, public health needs, and regulatory processes. A key challenge identified was the continued need for harmonization of maternal adverse event following immunization (AEFI) research and surveillance efforts within developing and developed country contexts. We conducted a systematic r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 41 publications
(30 citation statements)
references
References 80 publications
0
29
0
1
Order By: Relevance
“…Perhaps the most important limitation of existing studies of the association between influenza and adverse pregnancy outcomes is the inconsistency in case definitions of these adverse outcomes [65]. Even during the most recent pandemic in 2009 only a small number of studies actually specified the definitions used to classify gestational age dependent outcomes (e.g.…”
Section: Effects Of Influenza Virus Infection During Pregnancy On mentioning
confidence: 99%
“…Perhaps the most important limitation of existing studies of the association between influenza and adverse pregnancy outcomes is the inconsistency in case definitions of these adverse outcomes [65]. Even during the most recent pandemic in 2009 only a small number of studies actually specified the definitions used to classify gestational age dependent outcomes (e.g.…”
Section: Effects Of Influenza Virus Infection During Pregnancy On mentioning
confidence: 99%
“…Selected published works include randomized controlled vaccine trials, observational studies, and review articles, identified in a previous review 32 . A detailed search strategy and study inclusion criteria for this review was derived from previous work, including a systematic review of vaccine safety data reporting 34 and a systematic review documenting the extent and variability in adverse events following immunization (AEFIs) in maternal and neonatal clinical trials 32,34 . Study selection criteria are presented in Table 3.…”
Section: Methodsmentioning
confidence: 99%
“…Additional research, review of supplementary materials, and correspondence with study investigators could produce new categories of ethical issues that were not included in this report. Third, this review was limited to publications that met the inclusion criteria from a previous systematic review of AEFIs in vaccine studies involving pregnant women 32 . Publications meeting the inclusion criteria consisted largely of RCTs, cohort studies, and literature reviews, and do not include any editorial or commentary pieces published in peer-reviewed journals or other sources (Table S1).…”
Section: Limitationsmentioning
confidence: 99%
“…Indeed, the absence of global standard definitions for adverse events following immunization in pregnant women limits comparisons between safety data across studies and regions and, therefore, the performance of meta-analyses [100,101]. To facilitate comparison of data across clinical trials and observational studies, the Global Alignment of Immunization Safety Assessment in Pregnancy (GAIA) initiative was launched by the Brighton Collaboration Foundation and the WHO [102].…”
Section: Safety Considerations About Maternal Immunizationmentioning
confidence: 99%